The Development of Banana Bunch Wrapper - Ahmad Fizar, Ahmad Hafiz; Basharie, Siti Mariam; Mohamad Nazri, Muhammad Fakhrul Asyraf; Abu Bakar, Asyiq Hazarith (Multidisciplinary Applied Research and Innovation, 2022)
Banana is one of the most known fruits in Malaysia for its richness in nutrients. However, bananas need to be well cared for by wrapping some of the bananas to prevent them from being attacked by diseases and pests. In this study, a two-meter long wrapping tool with a weight of less than 3 kg was developed to facilitate in the banana wrapping process. This tool consists of a stick, lever, and two hooks as the main components. Once the plastic bag and a rubber strap are in place, the tool is ready to be used. The lever should be pulled as soon as the plastic bag covers the banana bunch. By pulling the lever, the iron string that is attached to the hook will pull the hook upwards and close it. The rubber strap will moves and ties the plastic when the hook is closed. The design of the tool and each part are drawn by using Solidworks for precise sizing. The performance test has been performed and the average wrapping time is approximately 40% less than the conventional method. This tool is practical and convenient to use. With its simplicity, it will benefit the farmers and agriculture industries.